Promote and to Create the Production of Films and Television Dramas Using Historical Data, Way of Life, The Culture of Communities Related to Isan Food Identity. - Laoakka, Sastra (Journal of Fine and Applied Arts Khon Kaen University, 2023)
Promote and to create the production of films and television dramas using historical data, way of life, the culture of communities related to Isan food identity. Is a research with two important objectives which are (1) to study of historical data, way of life, the culture of communities related to Isan food identity and (2) to propose guidelines for promoting Used to create the production of movies and television dramas using historical data, way of life, the culture of communities related to Isan food identity,This research uses basic research. The research has divided the target groups for data collection into 3 groups which are 1) Knowledge group 2) Practice group and 3) General person by collecting data from Document Collect data from field study by preliminary survey Structured and unstructured interview Observe with participation and without participation. Group conversation And analyze the data to find a way to answer the problems according to the set objectives. The results of the research revealed that the identity of the community is related to the 8 types of Thai food culture which are 1) Taiyo food, 3 distinctive food items 2) 3 types of Phu Thai people food 3) Food of Nga or Lao 1 Type 4) The food of Dan Sai people in Loei province is Saton vegetable juice. Guidelines for promoting Used to create the production of movies and television dramas using historical data, way of life, the culture of communities related to Isan food identity, as follows: 1. Establish information system In the aspects of history, art, culture and community identity related to Thai food culture To provide sufficient facilities for film and television drama producers to provide sufficient 2. Coordination between communities with government agencies, private organizations and film and television drama producers involved For proactive planning To develop sustainably 3. Set up a budget to support By teaching people in the community to collect information and present themselves For sustainable development.